To reveal disease or to promote function - that is the question - Eivind Meland; Stefan Hjörleifsson (Taylor & Francis Group, 2024)
AbstractMedicine faces challenges that indicate that it may not be sustainable. A descriptive disease concept is apt to what philosopher of science Ian Hacking called "looping effects", which can explain why health care is faced with insatiable demands. Diseases are not only indifferent objects with an objective existence in the biology of individuals. They are often interactive identities that have attractive properties. We suggest a shift in medical practice where descriptive perspectives are complemented with functional perspectives to enable clinicians better to help people from merging with dysfunctional disease identities.